Do Temporal and Spatial Parameters or Lifestyle of the Pacific Oyster Crasssostrea gigas Affect Pollutant Bioaccumulation, Offspring Development, and Tolerance to Pollutants? - Gamain, Perrine; Cachot, Jérôme; Gonzalez, Patrice; Budzinski, Hélène; Gourves, Pierre-Yves; Morin, Bénédicte (Frontiers in Marine Science, 2017)
This study evaluated the vulnerability of early life stages of native oysters (Crassostrea gigas) from the Arcachon Bay (SW, France) to pollutants at risk in the lagoon in particular copper and S-metolachlor. Developmental abnormalities in wild and cultivated oyster D-larvae were investigated during 2 breeding-seasons (2013 and 2014) at different sampling sites and dates. In addition, copper and metolachlor concentrations were determined both in seawater and in mature oysters. Bioaccumulation of Cu was observed at higher levels in wild than in farmed specimens. Metolachlor was accumulated at much lower levels. After 24h exposure, significant increases of the percentage of abnormal D-larvae were observed when exposed at 1 µg L-1 of copper or 10 ng L-1 of metolachlor in comparison with the controls whatever the date, the site and rearing conditions of the genitors. The current study demonstrates that environmental concentrations of copper and metolachlor can induce a significant increase of developmental abnormalities in farmed and wild populations of oysters. However, no significant differences of sensitivity were observed according to temporal, spatial parameters and lifestyle of genitors. In addition, oyster larvae obtained from the hatchery displayed the same sensitivity to pollutants as larvae from the field, demonstrating their suitability for toxicity assays and water quality monitoring.